2018
DOI: 10.5194/tc-12-3617-2018
|View full text |Cite
|
Sign up to set email alerts
|

Interannual snow accumulation variability on glaciers derived from repeat, spatially extensive ground-penetrating radar surveys

Abstract: Abstract. There is significant uncertainty regarding the spatiotemporal distribution of seasonal snow on glaciers, despite being a fundamental component of glacier mass balance. To address this knowledge gap, we collected repeat, spatially extensive high-frequency ground-penetrating radar (GPR) observations on two glaciers in Alaska during the spring of 5 consecutive years. GPR measurements showed steep snow water equivalent (SWE) elevation gradients at both sites; continental Gulkana Glacier's SWE gradient av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…Measurements of 1-year-old firn averaged 619 ± 47 kg m −3 (n = 8). Given the sustained mass loss of Pacific Northwest glaciers (Bolch et al, 2010;Menounos et al, 2019;Pelto, 2006), exposed firn is generally more than 1 year old, and we apply an uncertainty of 2 times the σ of our multi-year firn core observations (±15 %), which captures the range of observed firn densities (664-776 kg m −3 ). We use an ice density of 910 ± 10 kg m −3 (Clarke et al, 2013).…”
Section: Density Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements of 1-year-old firn averaged 619 ± 47 kg m −3 (n = 8). Given the sustained mass loss of Pacific Northwest glaciers (Bolch et al, 2010;Menounos et al, 2019;Pelto, 2006), exposed firn is generally more than 1 year old, and we apply an uncertainty of 2 times the σ of our multi-year firn core observations (±15 %), which captures the range of observed firn densities (664-776 kg m −3 ). We use an ice density of 910 ± 10 kg m −3 (Clarke et al, 2013).…”
Section: Density Estimatesmentioning
confidence: 99%
“…Random uncertainty stems from three sources that we assume to be independent: (i) elevation change uncertainty (σ h DEM ), (ii) glacier zone delineation uncertainty (σ A), and (iii) volume-to-mass density conversion uncertainty (σρ). We define σ h DEM following the methods detailed in Menounos et al (2019) and found an average decorrelation length of 0.75 km (Fig. S3).…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…At WG, ∼20 m amplitude drift and scour patterns characterize ∼20% of the accumulation zone ( Fig. 10a; McGrath and others, 2018). Safety and logistical practicalities prohibit the routine collection of a distributed set of measurements from this region, precluding an estimate of average mass within this region of extreme local variability.…”
Section: Elevation Dependencementioning
confidence: 99%
“…For example, expanded measurement networks and GPR analyses at GG and WG suggest that the long-term measurements underestimate accumulation (McGrath and others, 2018). Yet the same expanded networks and the geodetic calibrations suggest that the historically sparse networks underestimate ablation.…”
Section: Elevation Dependencementioning
confidence: 99%